STUDENT-TEACHERS’ PERSPECTIVES ABOUT INNOVATION IN ENGLISH LANGUAGE TEACHING (ELT) FOR ONLINE LEARNING - Irmawati; Santi Farmasari; Muhammad Isnaini; Edy Syahrial (Journal of English Education Forum (JEEF), 2022)
The impact of the corona virus pandemic (Covid-19) is now increasingly felt in the field of education, especially the change in teaching and learning modes, from offline learning to online. The online learning mode naturally brings uncomfortable adaptations among educators and students. Adaptation can relate to the literacy and competence of teachers in using online learning platforms and students' familiarity with online learning systems. This study aims at identifying and describing the students’ perspective on innovation in English language teaching (ELT) during the online learning. This study is a case study at 6th semester in English Education Study Program of Mataram University. This study uses qualitative methods and data collection techniques in this study are questionnaire and interview.